One Layer Object Separation Algorithm in Binary Image - Ratri Dwi Atmaja; Erwin Susanto; Junartho Halomoan; Muhammad Ary Murti (Institute of Advanced Engineering and Science, 2016)
We propose an algorithm to separate black object in binary image. The algorithm is designed to perform vertical separation first, then followed with horizontal separation. This process is done only once (one layer). Results showed that the algorithm potentially could be developed into n-layer separation in a recursive function. The algorithm also potentially could be developed in adaptive to determine when to use a vertical or horizontal separation first. It could be expected to reduce the recursive number.